2005
DOI: 10.1007/s10620-005-2902-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Glycoconjugate Content of Opossum Esophageal Epithelium and Glands: Regional Heterogeneity and Effects of Acid-Induced Mucosal Injury and Recovery

Abstract: This study examined the regional heterogeneity and site-specific changes in histology and glycoconjugate content following the induction of esophagitis and after recovery in an established animal model. Esophageal samples were excised from five sites in anesthetized opossums 24 hr after 3 consecutive days of 45-min perfusion with saline or 100 mM HCl or 1 week after acid in recovery animals. Controls exhibited significant regional differences in epithelial thickness, gland volume, glycoconjugate composition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It is well known that the protective potential of saliva within the esophageal lumen is enhanced by the secretion of esophageal submucosal mucus glands. 3,28 The salivary and esophageal secretions act in line to counteract the damage which might be caused by the endogenous and exogenous factors. In patients with reflux esophagitis, the secretion of protective factors of the esophageal submucosal mucous glands is diminished.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the protective potential of saliva within the esophageal lumen is enhanced by the secretion of esophageal submucosal mucus glands. 3,28 The salivary and esophageal secretions act in line to counteract the damage which might be caused by the endogenous and exogenous factors. In patients with reflux esophagitis, the secretion of protective factors of the esophageal submucosal mucous glands is diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in mast cell numbers have been reported in association with acid‐induced esophageal injury (5,9). We found no change in the number of mast cells at sites of experimental esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…We found no change in the number of mast cells at sites of experimental esophagitis. White et al (5) reported a decrease in the number of tissue mast cells associated with acute acid injury to the esophagus of the opossum. One explanation for this difference is in the method used to fix and examine tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations